Natural Occurrence, Exposure Assessment & Risk Characterization of Alternaria Mycotoxins in Apple By-Products in Argentina - Pavicich, Maria Agustina (2023)
Data on the natural occurrence of Alternaria mycotoxins in apple by-products is lacking in Argentina and the risk of exposure to these mycotoxins has not been characterized before. The levels of alternariol (AOH), alternariol monomethyl ether (AME), altenuene (ALT), tenuazonic acid (TeA), tentoxin (TEN), altertoxin-I (ATX-I), altertoxin-II (ATX-II), alternariol 3-sulfate (AOH-3-S), alternariol 3-glucoside (AOH-3-G), alternariol monomethyl ether 3-sulfate (AME-3-S), and alternariol monomethyl ether 3-glucoside (AME-3-G) were determined in clarifed and cloudy apple juices, marmalades, and applebased infant food from the Argentinean market, and the risk of exposure was characterized. Detectable levels of AME, TEN, TeA, AME-3-S and AOH-3-G were found in clarifed juices, while the same mycotoxins plus AOH were found in cloudy apple juices in higher concentrations. AME, TEN, TeA and AOH-3G were detected in marmalades, and AOH, AME, TEN and TeA in apple infant food. Probabilistic exposure assessment and risk characterization were carried out for children between 6 months and 5 years old in Argentina. The highest risk of exposure afected children between 6 and 23 months from the consumption of apple infant food and mainly associated with the alternariols. Better control strategies to prevent the incorporation of Alternaria mouldy core into the process line and the establishment of legislation for Alternaria mycotoxins are needed in Argentina.